PENGARUH OLAHRAGA INTENSITAS SEDANG TERHADAP PERUBAHAN EMOSI PADA LANSIA DI RANTING AISYIYAH CABANG MELATI - NANDA SYAVIRA; GUSBAKTI RUSIP (JURNAL ILMIAH SIMANTEK, 2020)
The elderly population is expected to increase over time. based on project's data, the prediction of increasing population in2020 reached 11.34% (27.08 million) people. the high number of Indonesian elderly not only has a positive impact in thefuture, but also negative impact. the elderly's problem are the aging process. aging is a process of physiological changesthat make body become weaker. the changes that shown in the body is physical functions, physical, cognitive, and even sosocial emotional. according to the centers for Disease Control and Prevention (CDC), moderate intensity exercise that beingcarried out regularly 3-5 times over 30 minutes that can provide benefit in emotional change. based on the introduction of theresearcher have described before, the researcher is interested to knowing the effect of moderate intensity exercise on theemotional change of elderly at the Pimpinan Ranting Aisyiyah Cabang Melati. To find out the influence between moderateexercise towards emotional change in elderly at Pimpinan Ranting Aisyiyah Cabang Melati. This study is experimental usingquasi experiment pre-test post-test control group design. Data are collected by ERQ quesionairre. Results of this researchused paired sample t test. Using paired sample t test analysis obtained the value P, p=0.001 in the group of respondentswho were given the intervention which means there is an effect between moderate intensity exercise towards emotional.There is an effect between moderate intensity exercise towards emotional change in Elderly at Pimpinan Ranting AisyiyahCabang Melati.